2020
DOI: 10.1038/s41379-019-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of differentiated dysplasia improves prediction of oral leukoplakia at increased risk of malignant progression

Abstract: Oral leukoplakia is the most common oral potentially malignant disorder with a malignant transformation rate into oral squamous cell carcinoma of 1-3% annually. The presence and grade of World Health Organization defined dysplasia is an important histological marker to assess the risk for malignant transformation, but is not sufficiently accurate to personalize treatment and surveillance. Differentiated dysplasia, known from differentiated vulvar intraepithelial neoplasia, is hitherto not used in oral dysplasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Oral leukoplakia is the most common precancerous lesion in the oral cavity with a global prevalence of 2–3% 6 . A recent study 7 on about 5000 individuals with leukoplakia has estimated that (a) only about one-third of individuals with leukoplakia develop oral cancer, and (b) the vast majority of individuals with leukoplakia who are found to progress to oral cancer develop the disease within 1 year of diagnosis of leukoplakia.…”
Section: Introductionmentioning
confidence: 99%
“…Oral leukoplakia is the most common precancerous lesion in the oral cavity with a global prevalence of 2–3% 6 . A recent study 7 on about 5000 individuals with leukoplakia has estimated that (a) only about one-third of individuals with leukoplakia develop oral cancer, and (b) the vast majority of individuals with leukoplakia who are found to progress to oral cancer develop the disease within 1 year of diagnosis of leukoplakia.…”
Section: Introductionmentioning
confidence: 99%
“…Wils et al recently reported on differentiated dysplasia, which is a subtype of dysplasia that is separate from the classic WHO definition and may be a more sensitive indicator to rule out concerning oral lesions. This dysplasia is characterized by “a basal layer of small cells with hyperchromatic or open nuclei with small nucleoli with an abrupt transition to suprabasal large cells with abundant, eosinophilic cytoplasm with differences in eosinophilia, intercellular edema, with clearly visible desmosomes, and large open nuclei with prominent nucleoli.” 13 In their study, when classic (WHO) dysplasia was ruled out, 11 of 56 progressed to cancer, but only two of 30 progressed to cancer when differentiated dysplasia was also ruled out. This is a new application to oral leukoplakia and it is not clear if it will become applied widely.…”
Section: Pathology Immunohistochemistry and Markersmentioning
confidence: 98%
“…Despite this, clinicians should be aware of some of these previous studies as they do provide information on leukoplakia pathophysiology. In a study by Wils et al, patients with no histological dysplasia who retained cytokeratin 13 (CK13) staining had significantly lower risk of progression to cancer 13 . Podoplanin is a lymphatic endothelial marker expressed in some cancers like esophageal cancer.…”
Section: Pathology Immunohistochemistry and Markersmentioning
confidence: 99%
“…Standard clinical policy is to take a biopsy to exclude invasive growth, which also allows grading for epithelial dysplasia on the basis of morphological abnormalities. Dysplasia is the best predictor of malignant transformation of leukoplakia, particularly when ‘differentiated dysplasia’, a novel morphological abnormality, is added [ 40 ].…”
Section: Field Cancerizationmentioning
confidence: 99%